24‐GHz Patch antenna array on cellulose‐based materials for green wireless internet applications. Issue 6 (1st November 2014) - Poggiani, Martina; Alimenti, Federico; Mezzanotte, Paolo; Virili, Marco; Mariotti, Chiara; Orecchini, Giulia; Roselli, Luca
Abstract : A 24‐GHz patch array antenna with integrated feeding network has been fabricated exploiting a multi‐layer cellulose‐based (i.e. paper) substrate. The adopted microstrip circuitry exploits a copper adhesive laminate that is shaped by a photo‐lithographic process and transferred to the hosting substrate using a sacrificial layer. The multi‐layer structure is obtained by stacking and gluing two layers of photo‐paper with an interposed copper ground plane. The measurements show an input reflection coefficient of about −29 dB at the centre frequency, an operating bandwidth with S 11 ⩽ −20 dB of 540 MHz and a gain of 7.4 dBi. The estimated radiation efficiency is 35%. The proposed design shows the feasibility of low‐cost antenna systems for green wireless internet technology and applications up to the boundary between microwaves and millimetre‐waves.